Development and Sustainable Growth of Mauritius
XXVI, 256 p. 15 illus., 4 illus. in color.
Keywords: This edited volume analyzes the Mauritius economy and highlights what conditions and policies have contributed to the development of the country. The project gives a historical and economic analysis of Mauritius and provides comparative approaches looking at other developing states in Africa and Asia. This book is intended for a broad audience, consisting of not only economists with quantitative expertise but also other social scientists, policymakers and scholars interested in the intellectually fascinating exploration of Mauritius’s rapid rise and sustained growth performance. Vanessa T. Tang is Research Lecturer in International Economics and Policy Development Consultant at the University of KwaZulu-Natal, South Africa. Timothy M. Shaw is Visiting Professor in PhD in Global Governance and Human Security at the University of Massachusetts, Boston, USA, and Emeritus Professor at the University of London, UK. Merle G. Holden is Emeritus Professor at the University of KwaZulu-Natal, South Africa.